Sistema objetual de ayuda en la prevención de crisis conductuales presentes en niños autistas (En un rango de 6-11 años) Grado 1 (2021)
The development of this project proposes the design of a device that helps in the therapy of children with ASD (Autism Spectrum Disorder), focused on mitigating the side effects that can cause behavioral crises, where they even reach self- and hetero-aggression, putting their lives at risk and that of others, This device must be present in long periods of their daily life to achieve confidence and attachment with the device in order to support the specialists contributing with afew moments of therapy at home, since one of the main problems is that the treatment is notcontinued at home with the necessary intensity.